PERSANDINGAN LEMBAGA OMBUDSMAN DAERAH ISTIMEWA YOGYAKARTA DENGAN OMBUDSMAN PERWAKILAN DAERAH PROVINSI - Noviana Noviana (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2021)
Provinsi Daerah Istimewa Yogyakarta memiliki dua lembaga pengawasan penyelenggaraan pelayanan publik yaitu Lembaga Ombudsman Daerah Istimewa Yogyakarta dan Ombudsman Perwakilan Daerah Provinsi sehingga perlu dikaji mengenai kedudukan hukum Lembaga Ombudsman Daerah Istimewa Yogyakarta dalam sistem otonomi daerah dan hubungannya dengan kedudukan Ombudsman Perwakilan Daerah Provinsi agar tidak terjadi pertentangan. Penelitian hukum normatif ini menggunakan metode pendekatan statute approach dan case approach. Hasil penelitian menunjukan bahwa Lembaga Ombudsman Daerah Istimewa Yogyakarta merupakan lembaga independen daerah sebagai salah satu wujud pengejawantahan asas desentralisasi dalam menyelenggarakan pemerintahan daerah pada kerangka otonomi daerah sedangkan Lembaga Ombudsman Daerah Istimewa Yogyakarta memiliki hubungan fungsional dengan Ombudsman Perwakilan Daerah Provinsi. Lembaga Ombudsman Daerah Istimewa Yogyakarta berbeda dengan Ombudsman Perwakilan Daerah Provinsi namun pengaturan mengenai lembaga ombudsman nasional, ombudsman perwakilan di daerah dan ombudsman daerah masih tumpang tindih antara satu dengan yang lain serta Undang-Undang Nomor 23 Tahun 2014 belum memberikan pengakuan terhadap lembaga ombudsman yang dibentuk oleh pemerintah daerah.The Special Region of Yogyakarta has two institutions to supervise the implementation of public services, namely The Special Region of Yogyakarta Ombudsman Institute and the Provincial Representative Ombudsman so that it is necessary to study the legal position of the The Special Region of Yogyakarta Ombudsman Institute in the regional autonomy system and its relationship to the position of the Provincial Representative Ombudsman so that there is no future conflict. This normative legal research uses a statute approach and a case approach. The results showed that The Special Region of Yogyakarta Ombudsman Institute is a regional independent institution as a manifestation of the decentralization principle in administering regional governance in the framework of regional autonomy, while The Special Region of Yogyakarta Ombudsman Institute has a functional relationship with the Provincial Representative Ombudsman. The Special Region of Yogyakarta Ombudsman Institute is still different from the Provincial Representative Ombudsman, but the regulations regarding the national ombudsman, regional representative ombudsman and regional ombudsman still overlap with one another and Law Number 23 of 2014 has not given recognition to the ombudsman institution established by regional government.